Peningkatan Kesadaran Masyarakat Terhadap Hiperurisemia Melalui Pemeriksaan Asam Urat dan Edukasi Gaya Hidup Sehat di Yayasan Baptis Cengkareng - Tjie Haming Setiadi; Alexander Halim Santoso; Edwin Destra; Steven Hizkia Lucius; Ryan Dafano Putra Mahendri; Andrew Philo (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
Uric acid is the final product of purine metabolism, which can increase due to high purine intake or impaired renal excretion. Accumulation of uric acid in the body is at risk of causing joint inflammation and other metabolic disorders. Early detection and dietary education are strategic steps to prevent complications of hyperuricemia. This activity uses the Plan-Do-Check-Act (PDCA) approach by examining uric acid levels using POCT and education on managing purine consumption. The examination was carried out on 62 adult participants. Educational leaflets were delivered directly and individually to each participant. All participants had uric acid levels in the normal range (median 4.2 mg/dL), with the lowest value of 3.5 mg/dL and the highest 6.5 mg/dL. Most participants were women and were in the middle to elderly age group. Although no cases of hyperuricemia were identified, preventive education remains essential to maintain uric acid levels within optimal ranges and reduce future metabolic risks. Lifestyle interventions focusing on diet and hydration are critical for sustainable uric acid control and long-term health outcomes. Keywords: Uric Acid, Purine, Hyperuricemia, Diet, Nutrition Education